E-Payment Transaction and Consumer Behaviour: A Study of Touch 'n Go e-Wallet During The COVID-19 Pandemic in Malaysia - Varieya Boon; Vishalini Devi A/P Sager; Umayrah Binti Amir Razif Arief; Vikniswaran A/L Hari Raman; Jimoh Adams Lukman; Yee Huei Lok (Global Academia Publisher, 2022)
The COVID-19 pandemic changed the way people do things and reframed the buyer perceptions. Malaysians have been urged to utilize e-Wallets instead of paper money in their daily transactions as a precautionary measure against health threats. Previously, Malaysians perceived e-Wallets as inconvenient and pointless. With the implementation of MCO (Movement Control Order), CMCO (Conditional Movement Control Order) and RMCO (Recovery Movement Control Order) by the government to stop the spreading of the COVID-19 virus, Malaysia started unlocking the e-Wallet emerged as a new normal for consumers. This study aims to examine the consumers' behaviour regarding the use of Touch 'n Go e-Wallet during the COVID-19 pandemic in Malaysia. The study employed a quantitative method of research while a questionnaire is used to elicit information from the respondents. This survey is expected to be completed by a total of 150 respondents through an online survey form, which is on the Google Form. The results are expected to provide insight into the users’ preferences and satisfaction with Touch 'n Go e-Wallet. Keywords: Consumer behaviour, Consumer satisfaction, e-Payment transaction, e-Wallet, COVID-19 pandemic, Malaysia.